2018
DOI: 10.1111/cch.12555
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the perspectives of 10‐, 11‐, and 12‐year‐old primary school students on physical activity engagement—“'Cause you can't just be sitting at a desk all the time!”

Abstract: These student perspectives and related recommendations may be beneficial for administrators and teachers in similar contexts who are seeking to enhance PA engagement among students with the goal of improving child health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 19 publications
0
56
0
Order By: Relevance
“…Teachers provided opportunities for children to influence the quality of their own participation in ways that treated children's perspectives as legitimate and worthy of notice. Letting children shape their experiences by adjusting challenge levels, who they played with, as well as the content of games and 'free time' activities mattered greatly to the children who thrived on increased opportunities and autonomy to make choices about their experiences, and to contribute to their participation (Harvey et al 2018).…”
Section: Collaboration On Learning Processes Matteredmentioning
confidence: 99%
“…Teachers provided opportunities for children to influence the quality of their own participation in ways that treated children's perspectives as legitimate and worthy of notice. Letting children shape their experiences by adjusting challenge levels, who they played with, as well as the content of games and 'free time' activities mattered greatly to the children who thrived on increased opportunities and autonomy to make choices about their experiences, and to contribute to their participation (Harvey et al 2018).…”
Section: Collaboration On Learning Processes Matteredmentioning
confidence: 99%
“…This corroborates with the findings of a systematic review of qualitative studies exploring the barriers and facilitators relating to children’s PA conducted by Brunton et al ( 2003 ), where fun and enjoyment were compelling reasons for the children’s participation in sports and exercise (Brunton et al, 2003 ). This idea is further supported by recent qualitative studies, which found that one of the main facilitators of PA was the enjoyment of activities (Abdelghaffar et al, 2019 ; Harvey et al, 2018 ; Van Den Berg et al, 2018 ; Wang et al, 2020 ). It is possible for this finding to be explained by the self-determination theory, which differentiates between autonomous and controlled forms of motivation (Ryan & Deci, 2017 ).…”
Section: Discussion and Recommendationsmentioning
confidence: 66%
“…A handful of children highlighted the availability of their peers, both from school and those living in the vicinity of their homes, as being an important factor in determining their engagement in PA outside of school. Friends are pivotal in making PA fun (Carlin et al, 2015 ; Corder et al, 2015 ), and thus children are more likely to be active when they are with their peers and friends in comparison to when they are alone (Harvey et al, 2018 ). This also accords to our earlier findings, in which fun and enjoyment strongly compel children to engage in PA.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Active involvement in decisions related to their participation, using approaches 'as close to the learners as possible' (Ennis 2017, 247) can increase ownership, investment and meaningfulness of physical education (Beni, Fletcher, and Ní Chróinín 2017;Enright and O'Sullivan 2010;Gray, Treacy and Hall 2019;Mikalsen and Lagestad 2020;Walseth, Engebretsen, and Elvebakk 2018). Pupils want increased opportunities and autonomy to make choices about their experiences, and to contribute to the planning and delivery of physical education (Harvey et al 2018). Following Quennerstedt (2019) we agree that 'children should not be positioned as not-yets, or as in-need in education … Instead children's views, needs and perspectives should be taken into account released from a pre-determined notion of adulthood' (613).…”
Section: Democratic Approaches Facilitate Personalisation Of Experiencementioning
confidence: 99%